Digital Nurturing Reinventing Motherhood in Digital Media Practices in the Asia-Pacific Region - Dong, Yu (Transactions on Social Science, Education and Humanities Research, 2023)
This study examines how digital parenting influences and reinvents traditional notions and roles of "motherhood" in digitally mediated practices in the Asia-Pacific region. With the widespread use of digital technologies in education, entertainment and socialisation, parenting practices and mothering roles are undergoing profound changes. Through a literature review and field case studies, this study examines how digital media have shaped new expressions of motherhood in the digital age, and how digital parenting has affected family, social and gender roles. The study found that digital parenting empowers motherhood with more flexibility and engagement, but also brings new challenges, such as the digital divide and privacy issues. In addition, digital parenting has triggered a rethinking of the traditional definition of motherhood, emphasising the synergy and balance of parental roles in the family. However, the practice of digital parenting is still evolving, and more interdisciplinary research is needed to delve into its lasting impact on social structures and family relationships.